Maltrato familiar y rendimiento escolar de los alumnos de cuarto año de secundaria - Institución Educativa N° 80756, Distrito El Porvenir, año 2017. - Ríos Gutiérrez, Arlyn Marigi (2019)
The present thesis was carried out with the purpose of analyzing the influence of family abuse on the school performance of the students of the fourth year of high school of the Educational Institution N ° 80756 "José María Arguedas", El Porvenir District, year 2017. The type of applied research has been considered, based on an explanatory design, and the sample consisted of 21 students, with whom we worked applying the methods and techniques of quantitative research: Statistical method and as a technique to the survey, and the qualitative research: Inductive - deductive method; and as techniques direct observation and interview. From the results obtained, it can be shown that these investigated students have a deficient relationship with their parents and are victims of physical abuse. This lack can be due to multiple circumstances in which adolescents are emotionally neglected and the relationships in which they interact with them will affect their school performance. Finally, we recommend that the educational authorities should hold meetings with the parents and orient them on the importance of preventing family violence, together with the students to improve the family climate and determine the support that should be given to families with this type of problem that affects school performance. The present thesis is subdivided into: Chapter I. Introduction: Problematic reality, antecedents, theoretical bases and conceptual framework. In te Chapter II, the methodology is presented; which was applied the statistical method and as a technique the survey and observation. In te Chapter III, the presentation of results is shown. In the Chapter IV, the discussion of results is presented.